HD'S TRILOGY: MODERN GNOSTICISM? - Brown, Dennis (Literature and theology, 1996)
The article outline the thematic development of HD's sequence of poems Triligy. It uses the term ‘Gnosticism’ to point up its religious character in terms of personal knowledge, ‘feminine’ values, Hellenistic syncretism and dualistic oppositionality predicated on a resurrectional dynamic. It also suggests its therapeutic quality in using a poetic of religiois discourse to create a healing affect, as it progresses from the evocation of the Blitz to a vision of renewal. The paper seeks to draw it to suggest the generally ‘gnostic’ condition of postmodern religious thought.